PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSETS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Ahmad Khusnaini, 14.05.52.0050; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study is a research that examines and analyzes the effect ofcurrent ratio, debt to equity ratio, return on assets and size on stock returns in manufacturing companies listed on the Indonesia Stock Exchange 2014-2016. This study uses purposive sampling method in sample selection. Based on the sample criteria, a sample of 222 to 178 companies was obtained during the three-year observation period. The analytical tool used is multiple linear regression analysis method. The results showed that the current ratio had a significant negative effect on stock returns, debt to equity ratio had no significant negative effect on stock returns, return on assets had a significant positive effect on stock returns and the size had no significant negative effect on stock returns. Keywords: Stock Return, Current Ratio, Debt to Equity Ratio, Return on Assets and Size